A τ-Tilting Approach to Dissections of Polygons - Pilaud, V.; Plamondon, P.-G.; Stella, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We show that any accordion complex associated to a dissection of a convex polygon is isomorphic to the support τ-tilting simplicial complex of an explicit finite-dimensional algebra. To this end, we prove a property of some induced subcomplexes of support τ-tilting simplicial complexes of finite-dimensional algebras.